2018
DOI: 10.2174/1568026618666181115102518
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Assessment in Pre-clinical Tests and in Clinical Trials: A Critical Review

Abstract: The identification of anxious symptoms is crucial to diagnose anxiety disorders, as well as to monitor their treatment in clinical practice and research. The aim of this review is to discuss the different ways of assessing anxiety in clinical research, including clinical trials, and the different kinds of animal behavioral tests used to study anxiety and test the efficacy of anxiolytics in pre-clinical studies. In clinical practice, a categorical classification (such as the Diagnostic and Statistical Manual of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
2
14
1
1
Order By: Relevance
“…As shown in Figure 3A (inferior panels), we found that during the exploratory hour, untreated surgery animals spent less time (p ≤ 0.015) in the center of the cage, but this behavior was not observed in animals treated with oxytocin (p = 0.929). Certainly, under light conditions, anxious animals tend to exhibit minimal exploratory behavior; thus, spending less time in the center is predictable (Castanheira et al, 2018). Accordingly, during the dark phase we did not find a substantial statistical effect before and after surgery, although a slight increase in this variable was observed in the oxytocin-treated animals (p = 0.073).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…As shown in Figure 3A (inferior panels), we found that during the exploratory hour, untreated surgery animals spent less time (p ≤ 0.015) in the center of the cage, but this behavior was not observed in animals treated with oxytocin (p = 0.929). Certainly, under light conditions, anxious animals tend to exhibit minimal exploratory behavior; thus, spending less time in the center is predictable (Castanheira et al, 2018). Accordingly, during the dark phase we did not find a substantial statistical effect before and after surgery, although a slight increase in this variable was observed in the oxytocin-treated animals (p = 0.073).…”
Section: Discussioncontrasting
confidence: 55%
“…In all cases we measured the horizontal activity (total distance), vertical episodes (rearing), and time (seconds) spent in the center of the open-field system. Indeed, horizontal and vertical activity have been proposed as an endpoint to indirectly analyze potential analgesic compounds ( Imanaka et al., 2008 ; Majuta et al., 2017a ), whereas time spent in the center has been used as an endpoint to analyze anxiety-related effects ( File, 1980 ; Castanheira et al., 2018 ), a key issue after postoperative pain ( Carr and Goudas, 1999 ; Kehlet and Dahl, 2003 ; Kouya et al., 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…We found that 1-hour 1% sevo urane inhalation for 5 days reversed the decreases in locomotion and sociability induced by MK801. OFT was adopted to access the exploratory behaviors and emotional disorders including anxiety-like and depression-like behaviors 19,20 , whilst an automated three-chambered social approach task was used for evaluating sociability 21 . Our results are in agreement with studies showing that administration of MK801 to neonatal animals induced reduction in spontaneous locomotor activity in long-term which may re ect psychomotor retardation 22,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The OFT is widely used to assess individual spontaneous locomotor activity and anxiety-like behavior when animals are introduced to a novel environment ( Prut and Belzung, 2003 ; Bailey and Crawley, 2009 ; Castanheira et al., 2018 ). Importantly, this test allows to detect bias in animal behaviour that could affect performance on NORT, since locomotor activity can impact exploratory drive ( Broadhurst, 1957 ; Broadhurst, 1958 ).…”
Section: Methodsmentioning
confidence: 99%